2022
DOI: 10.23887/paud.v10i1.47346
|View full text |Cite
|
Sign up to set email alerts
|

Video Animasi Mengenal Huruf dan Angka untuk Menstimulus Kemampuan Kognitif dan Bahasa Anak Usia Dini

Abstract: Sebagian anak-anak mengalami kesulitan dalam mengingat ataupun mengenal huruf dan angka. Hal ini dikarenakan cara penyampaian dan media yang digunakan masih kurang menarik. Penelitian ini bertujuan mendeskripsikan rancang bangun dan menguji kelayakan media pembelajaran berbasis video animasi mengenal huruf dan angka untuk menstimulasi kemampuan kognitif dan bahasa pada anak usia dini. Jenis penelitian ini adalah penelitian pengembangan dengan model ADDIE. Pengguna dan ahli ini adalah ahli isi pembelajaran, ahl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Meanwhile, factors that come from outside the reader (external) include external encouragement, such as giving gifts or the like given by the teacher at a certain time (Afrianti & Marlina, 2021;Apriliana & Berlianti, 2018). Using animated video media increases students' enthusiasm when participating in learning (Oktafiyana & Septiana, 2021;Swari & Ambarawa, 2022;Yuniarni et al, 2020). Previous research findings also revealed that animated video media increased students' enthusiasm (Masykuroh & Khairunnisa, 2022;.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, factors that come from outside the reader (external) include external encouragement, such as giving gifts or the like given by the teacher at a certain time (Afrianti & Marlina, 2021;Apriliana & Berlianti, 2018). Using animated video media increases students' enthusiasm when participating in learning (Oktafiyana & Septiana, 2021;Swari & Ambarawa, 2022;Yuniarni et al, 2020). Previous research findings also revealed that animated video media increased students' enthusiasm (Masykuroh & Khairunnisa, 2022;.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research findings also reveal that animated videos are a medium that can facilitate the delivery of information or messages to students (Candra Dewi & Negara, 2021;Fauziah & Ninawati, 2022;Khairani et al, 2019;Swari & Ambarawa, 2022). This animated video media can be used in the learning process so that the learning process can take place effectively and pleasantly with the Directed Reading Thinking Activity (DRTA) strategy focusing on student activities when reading a reading text.…”
Section: Introductionmentioning
confidence: 99%
“…The development of education is technological progress, where the current situation of all elements must be able to keep up with existing technological advances over time, so the use of technological media such as animation in learning is very important (Irawan et al, 2022;Solfiah et al, 2021;Susilawati & Satriawan, 2020). There are still many teachers who think that learning media such as animation is not very important in learning, most think that the use of media such as animation in learning only adds to the burden on facilities and infrastructure in delivering learning (Mutiara & Yatri, 2022;Swari & Ambarawa, 2022). Even though animated films have advantages compared to other media, because they combine audio-visual in one medium (Khairunnisa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Language plays an important role as a conversational tool through which individuals and groups convey ideas, listen to conversations, exchange opinions, read and write, and give rise to thoughts and feelings about individuals and groups. Therefore, language learning has many benefits for students, so students need to teach it well (Abidin et al, 2022;Bonafix & Manara, 2016;Susmiati, 2020;Swari & Ambarawa, 2022). Language is the main communication tool in students' daily lives.…”
Section: Introductionmentioning
confidence: 99%